Prospects and Implications of Turkish–Egyptian Reconciliation. (September 2022) - Yeşilyurt, Nuri; Magued, Shaimaa
This commentary explains various implications of a possible Turkish–Egyptian reconciliation. Based on an extensive analysis of Turkish and Egyptian newspapers and open-ended and semi-structured in-depth interviews, this commentary addresses the significance of a Turkish–Egyptian reconciliation for both countries, its regional implications and the prospects for bilateral relations. In this context, the commentary discusses the domestic, bilateral and regional implications of a prospective reconciliation between Turkey and Egypt.